A Bibliometric Survey of Metadiscourse (1979-2023): Looking behind to Look Ahead - Li, Gaoxin; Xu, Jinfen (Círculo de Lingüística Aplicada a la Comunicación, 2024)
This paper aims to present a systematic overview of metadiscourse discourse studies published in different sources, examine the structure of scientific collaboration, identify hot research areas, and trace the research trends. To meet this objective, the bibliometric records of metadiscourse-related publications are first retrieved from the Web of Science Core Collection. Then, the bibliometric analysis and social network analysis are employed to analyze the retrieved bibliometric databased with bibliometrix and VOSviewer. Our bibliometric analysis shows that the overall trend of metadiscourse-related publications has been on the increase, with a relatively slow growth before 2011. It also identifies the most productive journal, the top prolific author, the top productive institution and country. On the other hand, the social network analysis yields collaboration networks, and keyword-based co-occurrence networks. The collaboration networks show the most fruitful co-author collaboration network, and the most productive co-institution network, and the most productive co-country network. The keyword-based co-occurrence network sketches major research areas and detects their changing trajectory. Hence, the findings are expected to help orient novice researchers to metadiscourse studies, and offer the insights for future researcher to address the emerging issues of metadiscourse.